Impact of mixed perovskite composition based silicon tandem PV devices on efficiency limits and global performance. (December 2022) - Baloch, Ahmer A.B.; Albadwawi, Omar; AlShehhi, Badreyya; Alberts, Vivian
Abstract: Optical and electrical features of halide perovskites make them commercially attractive high-efficiency solar cell absorbers. As a result, perovskite/silicon tandem solar cells have recently garnered the scientific community's attention due to their better efficiency than single-junction solar cells. The most researched perovskite solar cell (PSC) is based on methylammonium lead iodide perovskite type; nevertheless, mixed cation/anion perovskites show better performances. Compositional engineering of perovskite allows us to screen for more efficient and stable materials. To better understand perovskite/silicon tandem performance, we systematically analyse the impact of compositions on device output under standard testing conditions and real-world climate using an opto-thermal model. Regional cell temperature and energy yield potential for variable perovskite compositions and bandgaps, FA x MA (1−x) Pb(Br y I (1−y) )3, are investigated. The optimal band gaps for bottom cells using Si (1.12 eV) and perovskite top cells (around 1.5–2.1 eV) are studied for realistic climate conditions. With a bandgap of 1.7 eV, the compound MAPbBrI 2 exhibited the best opto-electronic performance in tandem cells. Globally, Perovskite/silicon tandem cells (except 2.1 eV top cell perovskite) performed thermally better than Silicon solar cells due to the increased efficiency of tandem devices. The world-wide average perovskite cell temperature reduction was −3.9 °C, whereas the average energy generated was 26.7% higher relative to silicon solar cells. The current study will be extended by analysing the temperature coefficient's sensitivity and employing realistic solar cell architectures.